THE PHYSIOLOGICAL AND PSYCHOSOCIAL CONSEQUENCES OF INFANTILE OBESITY (CIPEEX, 2022)
CHILDHOOD OBESITY IS CONSIDERED A WORLDWIDE PUBLIC HEALTH PROBLEM BY WHO. IT IS A MULTIFACTORIAL DISEASE THAT INVOLVES METABOLIC, GENETIC, ENVIRONMENTAL AND SOCIOECONOMIC DISORDERS. THE OBJECTIVE IS TO ESTABLISH DIRECT AND INDIRECT RELATIONSHIPS BETWEEN CHILDHOOD OBESITY AND ITS VARIOUS IMPLICATIONS, BOTH PHYSIOLOGICALLY AND PSYCHOSOCIALLY. THE PRESENT WORK DEALS WITH AN EXPANDED SUMMARY, USING THE MOST RECENT ARTICLES COLLECTED IN PLATFORMS SUCH AS SCIELO AND PUBMED, WHICH MAKE RELATIONSHIPS BETWEEN OBESITY AND ITS VARIOUS IMPLICATIONS. THE SEARCH PERIOD OF THIS RESEARCH WAS BETWEEN 2014 AND 2018. IT WAS FOUND THAT OBESE CHILDREN ARE MUCH MORE LIKELY TO DEVELOP VARIOUS DISEASES, SUCH AS DYSLIPIDEMIAS, TYPE 2 DIABETES, DEPRESSION, AMONG OTHERS, REQUIRING INTERVENTIONS THE FASTEST POSSIBLE. IT IS CONCLUDED, THEREFORE, THAT CHILDHOOD OBESITY IS RESPONSIBLE FOR MULTIPLE NEGATIVE CONSEQUENCES, BOTH SOCIAL AND PHYSICAL, IN THE LIVES OF MILLIONS OF CHILDREN.
Keywords: Pediatric obesity. Metabolic syndromes. Respiratory diseases. Neurobehavioral manifestations.